Time lag between metamorphism and crystallization of anatectic granites (Córdoba, Argentina) - D’Eramo, F, J. (2020)
SHRIMP and LA-ICP-MS analyses carried out on zircons from the Río de los Sauces granite revealed their metamorphic and igneous nature. The metamorphic zircons yielded an age of 537±4.8 (2σ)Ma that probably predates the onset of the anatexis during the Pampean orogeny. By contrast, the igneous zircons yielded a younger age of 529±6 (2σ)Ma and reflected its crystallization age. These data point to a short time lag of ca. 8Myr between the High Temperature (HT) metamorphic peak and the subsequent crystallization age of the granite. Concordia age of 534±3.8 (2σ)Ma, for both types of zircon populations, can be considered as the mean age of the Pampean HT metamorphism in the Sierras de Córdoba.